Severe Psychomotor Delay in a Severe Presentation of Cat-Eye Syndrome - Guillaume Jedraszak; Aline Receveur; Joris Andrieux; Michèle Mathieu-Dramard; Henri Copin; Gilles Morin (Case Reports in Genetics)
Cat-eye syndrome is a rare genetic syndrome of chromosomal origin. Individuals with cat-eye syndrome are characterized by the presence of preauricular pits and/or tags, anal atresia, and iris coloboma. Many reported cases also presented with variable congenital anomalies and intellectual disability. Most patients diagnosed with CES carry a small supernumerary bisatellited marker chromosome, resulting in partial tetrasomy of 22p-22q11.21. There are two types of small supernumerary marker chromosome, depending on the breakpoint site. In a very small proportion of cases, other cytogenetic anomalies are reportedly associated with the cat-eye syndrome phenotype. Here, we report a patient with cat-eye syndrome caused by a type 1 small supernumerary marker chromosome. The phenotype was atypical and included a severe developmental delay. The use of array comparative genomic hybridization ruled out the involvement of another chromosomal imbalance in the neurological phenotype. In the literature, only a few patients with cat-eye syndrome present with a severe developmental delay, and all of the latter carried an atypical partial trisomy 22 or an uncharacterized small supernumerary marker chromosome. Hence, this is the first report of a severe neurological phenotype in cat-eye syndrome with a typical type 1 small supernumerary marker chromosome. Our observation clearly complicates prognostic assessment, particularly when cat-eye syndrome is diagnosed prenatally.